Extracorporeal lung support. Issue 1 (February 2017) - Salna, Michael; Bacchetta, Matthew
Abstract : Purpose of review: The applications for extracorporeal membrane oxygenation for lung support are constantly evolving. This review highlights fundamental concepts in extracorporeal lung support and describes directions for future research. Recent findings: Since the 1950s, extracorporeal lung support has experienced continuous advancements in circuit design and safety in acute respiratory distress syndrome, chronic obstructive pulmonary disease exacerbations, as a bridge to transplantation, intraoperative cardiopulmonary support, and for transportation to referral centers. Patients on extracorporeal membrane oxygenation are now capable of being awake, extubated, and ambulatory for accelerated recovery or optimization for transplantation. Summary: Extracorporeal lung support is a safe and an easily implemented intervention for refractory respiratory failure. Recent advances have extended its use beyond acute illnesses and the developments for chronic support will facilitate the development of durable devices and possible artificial lung development.